Solve for n -28-8n=-6(n+6)

Math
-28-8n=-6(n+6)
Simplify -6(n+6).
Tap for more steps…
Apply the distributive property.
-28-8n=-6n-6⋅6
Multiply -6 by 6.
-28-8n=-6n-36
-28-8n=-6n-36
Move all terms containing n to the left side of the equation.
Tap for more steps…
Add 6n to both sides of the equation.
-28-8n+6n=-36
Add -8n and 6n.
-28-2n=-36
-28-2n=-36
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 28 to both sides of the equation.
-2n=-36+28
Add -36 and 28.
-2n=-8
-2n=-8
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2n=-8 by -2.
-2n-2=-8-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2n-2=-8-2
Divide n by 1.
n=-8-2
n=-8-2
Divide -8 by -2.
n=4
n=4
Solve for n -28-8n=-6(n+6)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top